2006
DOI: 10.1088/1126-6708/2006/03/018
|View full text |Cite
|
Sign up to set email alerts
|

Planar Script N = 4 gauge theory and the Hubbard model

Abstract: Recently it was established that a certain integrable long-range spin chain describes the dilatation operator of N = 4 gauge theory in the su(2) sector to at least three-loop order, while exhibiting BMN scaling to all orders in perturbation theory. Here we identify this spin chain as an approximation to an integrable short-ranged model of strongly correlated electrons: The Hubbard model.Recently it was discovered that the planar one-loop dilatation operator of supersymmetric N = 4 gauge theory is completely in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
279
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(294 citation statements)
references
References 65 publications
11
279
1
3
Order By: Relevance
“…The curious numerical prefactor includues e = exp(1), the base of natural logarithm. This result is even more interesting when one compares it to finite size corrections for the magnon computed within the Hubbard model approach [36] which gives [36,35] …”
Section: Finite Size Correctionsmentioning
confidence: 95%
“…The curious numerical prefactor includues e = exp(1), the base of natural logarithm. This result is even more interesting when one compares it to finite size corrections for the magnon computed within the Hubbard model approach [36] which gives [36,35] …”
Section: Finite Size Correctionsmentioning
confidence: 95%
“…In appendix A we introduce the Dirac matrices for SO(5) γ s , s = 1, 2, 3, 4 and γ 5 ≡ , which we all take to be Hermitian. These matrices obey the relations 17) and, therefore, span the orthogonal complement to the Lie algebra so(5). The same matrices can be used to build the set of Dirac matrices for so(4, 1); one takes {i , γ a } with a = 1, 2, 3, 4.…”
Section: Superalgebra Psu(2 2|4)mentioning
confidence: 99%
“…This conjecture has been by now extended to the full P SU (2, 2|4) case in the gauge theory [16] and is believed to hold in an asymptotic sense, where the classical scaling dimension of the operator in question determines the loop order to which a prediction is made by the Bethe equations. Moreover, in the prominent minimal compact, bosonic subsector of SU (2) the conjectured gauge theory Bethe equations [15] were recently shown to arise microscopically from the well-known Hubbard model at half filling [17]. Whether this surprising connection is indeed fully realized beyond three loops remains to be seen; for this a four-loop computation on the gauge theory side would have to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…In [30,31] the classical algebraic curve for the string moving in S 5 ⊂ AdS 5 ×S 5 was obtained as the classical limit of the quantum nested Bethe ansatz equations coming from the Zamolodchikov's bootstrap procedure [32] where in addition to the magnons described by the roots u j we have the rapidities θ α of the relativistic particles with O(N) isotopic degree of freedom. In [33] it was observed that the BDS equations [6] mentioned in the introduction (1) could be obtained from the Hubbard model where the electron has a spin which can create spin waves described by the roots u j , but also has momentum p α . In both cases the introduction of the extra level simplifies the structure of the Bethe equations considerably.…”
Section: Speculations On Nestingmentioning
confidence: 99%